PENERAPAN PENDEKATAN TARL DALAM MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SD INPRES BERTINGKAT GOWA KABUPATEN GOWA - Ambiyah; Audry Aulia Nafasya; A. Siti Ashila Putri Ananta (STKIP Subang, 2024)
This research aims to determine and analyze the impact of implementing the Teaching at Right Level (TaRL) approach on the learning outcomes of Gowa Grade Inpres Elementary School students with a sample size of 30 students. The method used is classroom action research, which allows details of the implementation process, evaluation of changes, and identification of challenges in an effort to improve the quality of learning. This research was carried out in several cycles, each of which consisted of planning, implementation, observation and reflection. In implementing TaRL, the main focus is to adapt the learning approach to the individual student's level of understanding. Data was collected through classroom observations and assessment of learning outcomes. Preliminary results indicate an increase in student engagement and understanding of the material, as well as the challenges teachers face when adapting traditional teaching methods to TaRL concepts. Support from teachers and schools is very important in the successful implementation of TaRL. It is hoped that this research can deepen understanding of the effectiveness of TaRL in improving student learning outcomes. The practical implication is the importance of providing teaching that is more contextual, responsive to individual student needs, and encourages improvements in the quality of education. The research results showed an increase in student learning outcomes, where learning completeness increased from 40% in cycle I to 83% in cycle II.